Determinacion del contenido de materia seca y almidon en yuca por el sistema de gravedad especifica - Toro, Julio C.; Canas, A. (International Center for Tropical Agriculture, 1983)
The specific gravity technique (a simple and practical method) to determine DM and starch content in cassava roots is described; the materials used and the methodology are included. A conversion table to determine DM and starch percentage in cassava is given. (CIAT)